2008
DOI: 10.2166/wh.2008.054
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of analytical observational studies investigating the association between cardiovascular disease and drinking water hardness

Abstract: The aim of this study is to systematically review and critically assess analytical observational epidemiology studies investigating the association between levels of drinking water hardness and cardiovascular disease. We searched electronic databases and used standardised forms to extract data and assess study quality. Of 2,906 papers identified, 14 met the inclusion criteria (nine case control and five cohort studies). Of the nine case control studies, seven examined both drinking water magnesium and calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(56 citation statements)
references
References 41 publications
2
49
0
5
Order By: Relevance
“…Ca from food did not affect levels of total and LDL cholesterol. Results of this study are consistent with the results of many other published studies in which the inverse relationship between water hardness and cardiovascular morbidity and mortality was established [23][24][25]. Persons who consumed medium hard drinking water had a significantly higher rate of incidence of IHD compared to people of the same sex and age who consume hard drinking water.…”
Section: Resultssupporting
confidence: 91%
“…Ca from food did not affect levels of total and LDL cholesterol. Results of this study are consistent with the results of many other published studies in which the inverse relationship between water hardness and cardiovascular morbidity and mortality was established [23][24][25]. Persons who consumed medium hard drinking water had a significantly higher rate of incidence of IHD compared to people of the same sex and age who consume hard drinking water.…”
Section: Resultssupporting
confidence: 91%
“…In other cases, these essential elements are only limited in the form of recommended values, such as in the Slovak guideline for water used for human consumption [17]. There are many publications documenting increased incidence and mortality rates for cardiovascular diseases associated with a deficit of Ca and Mg in drinking water [18,19,20,21,22,23,24]. Several studies can be found that link these deficits to increased mortality from oncological diseases as well [25,26,27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have documented that softer water is associated with higher CVD death rates; this protective role is suggested to be because of the water Ca content [28, 29]. …”
Section: Discussionmentioning
confidence: 99%